2015
DOI: 10.1590/s0100-83582015000400018
|View full text |Cite
|
Sign up to set email alerts
|

Mobilidade Do Sulfentrazone Em Solos Com Diferentes Características Físicas E Químicas

Abstract: RESUMO -O conhecimento dos fatores que influenciam a lixiviação dos herbicidas no solo é fundamental para sua utilização de forma segura, do ponto de vista técnico e ambiental. Neste trabalho, avaliou-se a mobilidade do sulfentrazone em quatro solos provenientes de uma área de reflorestamento da região Sul do Brasil (Planossolo Háplico, Argissolo Vermelho, Cambissolo Húmico e Neossolo Regolítico) e um Latosso Vermelho-Amarelo da Zona da Mata de Minas Gerais. As amostras de solo foram coletadas na profundidade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
(18 reference statements)
0
5
0
5
Order By: Relevance
“…The adsorption of sulfentrazone to the soil is influenced by pH, organic matter and clay content Braga et al, 2016;Teixeira et al, 2017). Soils with lower clay and organic matter levels show high potential for sulfentrazone leaching (Faustino et al, 2015). Sulfentrazone was also applied under preemergence conditions of sunflower in clay soil (77.5% clay) (Brighenti et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption of sulfentrazone to the soil is influenced by pH, organic matter and clay content Braga et al, 2016;Teixeira et al, 2017). Soils with lower clay and organic matter levels show high potential for sulfentrazone leaching (Faustino et al, 2015). Sulfentrazone was also applied under preemergence conditions of sunflower in clay soil (77.5% clay) (Brighenti et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…However, herbicides with residual effects are an alternative practice in weed control in sunflower fields (Týr & Vavrík, 2015). The dynamics of these herbicides in soils are influenced by various characteristics, such as soil mineralogy, soil texture, moisture content, organic matter and pH Faustino et al, 2015). Thus, studies of herbicide selectivity as a function of specific conditions are necessary to avoid toxicity on sunflower plants and to obtain effective control of the main weed species.…”
Section: Introductionmentioning
confidence: 99%
“…Each fraction was placed in pots without drainage holes with a capacity of 300 cm 3 in which the bioindicator species sorghum (Sorghum bicolor) was planted. This species was used as a bioindicator of sulfentrazone in the soil because it is highly sensitive to the herbicide (Faustino et al, 2015;Silva et al, 2016;Madalão et al, 2017). For this reason, 7 seeds were added to the soil, and three seedlings were left after thinning.…”
Section: Methodsmentioning
confidence: 99%
“…Another fraction (250g) of each treatment was placed in pots of 300 cm 3 capacity, where the bioindicator Sorghum bicolor was planted. S. bicolor was selected as an indicator of sulfentrazone residues in soil based on several studies (Faustino et al, 2015, Silva Junior et al, 2016, Madalão et al, 2017 that confirmed the high sensitivity of this species to sulfentrazone.…”
Section: Soilmentioning
confidence: 99%